The impact of the school feeding program from the teachers' point of view on the effectiveness of students' learning and achievement- Mafraq Governorate schools in Jordan as a model - Al-Khalayleh, Atef AbdelKarim Ahmed (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the impact of the school feeding program on stimulating learning motivation and achievement among primary school students in Jordan, in the Mafraq Governorate, from the teachers' point of view. The researcher used the descriptive approach because it corresponds to the objectives of the study. To achieve this, the researcher designed a questionnaire that consisted of (20) paragraphs divided into two areas: the effect of healthy nutrition on academic achievement, and the effect of healthy nutrition on learning motivation, and after verifying its validity and stability, it was distributed to The study sample consisted of (100) teachers in the schools of the Mafraq district, who were randomly selected After conducting the statistical treatment, the results indicated that there is a medium degree for the effect of healthy nutrition as a whole, where the arithmetic mean of the effect of healthy nutrition for the study tools as a whole was (3.34). It also indicated that there were statistically significant differences at the significance level (α ≤ 0.05) in the effect of healthy nutrition as a whole, according to the age variable. In light of the results, recommendations were made, including: continuity of the school feeding program in schools, inclusion of different age groups in schools in the school feeding program, ensuring proper healthy nutrition for children and taking care of their nutrition at home and at school, as the responsibility of parents at home is great in preparing the appropriate food for their children.
Keywords: healthy nutrition; learning motivation; school; school nutrition